Journal: Safety Talk / Accident Investigations / Lessons In Prevention for Blasting Safety Managers - Ann Barron (International Society of Explosives Engineers, 2007)
Even though you think your company’s safety program is the best it can be, equipment, processes, supplies, surroundings and people do not always behave or react as expected. Consequently, needless accidents occur each year at quarries, construction sites, surface mines, and other locations where explosives are used. While blasting accidents account for only a small portion of the total accidents reported, the severity rate for blasting accidents is higher than for any other accident category.